Effect of high intensity interval training with blood restriction on anaerobic performance - Behi, A.; Fahey, T. D.; Afsharnezhad, T.; Amani, A. R. (International Journal of Applied Exercise Physiology, 2017)
Limiting venous blood flow restriction is a new approach of training aims to improving high level of performance among athletes, which has shown prominent results at muscle hypotrophy and strength. KAATSU[1] is a training system including pressure belt imposed on the proximal part of the upper and lower bodies. The present study aims to investigate the effect of HIIT Kaatsu trainings on anaerobic performance among young athletes. The present quasi experimental research was conducted through a pre-test and post-test and three groups including KAATSU intensive interval exercises (n=11), intense interval exercise (n=9) and a control group (n=10). The exercises included running distances of 20 and 40 meters. In the beginning of the protocol most of the exercises was in short distances and as the sessions proceeded, the number of the sets and repetitions increased and it reached to its highest intensity in the last session. During the exercise protocol, intensity of training was considered to be the highest running speed and based on their abilities each individual tried to run as fast as possible. The exercise load was defined based on repetitions and the sets. In the 20 meters distances, the participants took a ten second rest after each repetition and a one minute rest after each set and in 40 meters distances; Subjects took a 20 second rest after each repetition and 2 minute rest between sets. The control group did not performed any of the mentioned exercises. Moreover, before and after four weeks of training the individuals were given RAST and Anaerobic Biking Wingate Test. Statistical result has been shown, there is a significant change between the maximum anaerobic power in Wingate biking test after four weeks within KAATSU intensive interval (P= 0.05) and intensive interval (P= 0.05) groups, but no significant change was detected in the control group (P> 0.05). The statistical analysis of this research has been shown that there is of current investigation indicated that compared to intensive interval exercise alone, attending the KAATSU intensive exercises is more effective on the highest anaerobic power ( Wingate bike) and the lowest as well as the average of anaerobic power.